2016
DOI: 10.2139/ssrn.2737842
|View full text |Cite
|
Sign up to set email alerts
|

Female Labor Force Participation in Asia: Indonesia Country Study

Abstract: This paper uses over 20 years of data from Indonesia's labor force survey to study trends in female labor force participation (FLFP). We find that younger women in urban areas have increased their labor force participation in recent years, largely through wage employment, while younger women in rural areas have reduced their labor force participation, largely by opting out of informal, unpaid employment. We find evidence that wage jobs are more desirable than other types of work and that many women exit wage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 35 publications
3
75
0
9
Order By: Relevance
“…Arguably, in this era, the state both increasingly recognizes religious authority in its family law efforts as well as seeks Research shows that educated young women do not plan to give up their careers after marriage (Utomo 2015;. Women are gravitating toward the service sector, with 58% of working women in non-agricultural sectors (Schaner and Das 2016). In 2016, just 12% of Indonesians aged 25-34 had tertiary education, but the percentage of women among those enrolled in tertiary education rose from 9% in 1990 to 32% in 2012 (OECD 2016).…”
Section: Changes In Indonesian Muslim Family Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably, in this era, the state both increasingly recognizes religious authority in its family law efforts as well as seeks Research shows that educated young women do not plan to give up their careers after marriage (Utomo 2015;. Women are gravitating toward the service sector, with 58% of working women in non-agricultural sectors (Schaner and Das 2016). In 2016, just 12% of Indonesians aged 25-34 had tertiary education, but the percentage of women among those enrolled in tertiary education rose from 9% in 1990 to 32% in 2012 (OECD 2016).…”
Section: Changes In Indonesian Muslim Family Lawmentioning
confidence: 99%
“…Indonesian women, especially those in the middle class, have increasing work and educational opportunities.Indonesian women have long worked outside the house, but mostly in the informal and agricultural sectors. Indonesian women's labor force participation rose from 26% to 51.4% between 1971 and 2014, though it has not changed much since 1990(Schaner and Das 2016).…”
mentioning
confidence: 99%
“…The increasing exposure to equal opportunities of men and women could be indicated, to a lesser extent, by the rise of women's employment and educational attainment. Schaner and Das (2016) have reported that there is evidence of increasing participation of younger women living in the urban areas in wage employment. The study also found a narrowing trend in gen-der gap in wage employment-in 2011, the median women earned 84% as much as their male counterparts compared to 57% in 1990.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…The study also found a narrowing trend in gen-der gap in wage employment-in 2011, the median women earned 84% as much as their male counterparts compared to 57% in 1990. In 2011, almost 30% of women obtained senior secondary and post-secondary degrees compared to merely 11% of women in 1990 and around 8% of women had tertiary degree (Schaner & Das, 2016). Consequently, greater participation in wage employment has enabled them to be more economically independent, while better access to education has enriched them with better understanding of their worth.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…We can set the price of output 3 Note that the inelastic labor supply formulation is an attractive simplification to the model, but it is in stark contrast to the data in Indonesia. For example, currently, only 50 percent of women in Indonesia participate in the labor force (Schaner and Das, 2016). 4 In other words, ε has the following cumulative distribution function: F (ε) = exp {− exp {−ε/s}}.…”
Section: Firmsmentioning
confidence: 99%